LEGAL ANALYSIS OF LEGITIME PORTIE FOR CHILDREN IN INSIDE AND OUTSIDE LEGITIMATE MARRIAGE IN CIVIL CODE (BURGERLIJK WETBOEK) - Prasasti Dyah Nugraheni (Magister Hukum Sekolah Pascasarjana Unida, 2019)
Inheritance law in a Civil Code is one part of a civil law that has basic nature of regulating something and there’s no element of coercion in the inheritance law. Because this inheritance law is one part of a civil law that has basic nature of regulating, then in this inheritance law there are rules governing an heir to his assets as long as an heir’s still alive. To obtain an inheritance, it can be done in two ways, which include obtaining an inheritance based on the law and obtaining an inheritance based on a will. To obtain an inheritance based on the law, then there must be an absolute part (legitime portie) of an inheritance, namely the existence of an absolute part that’s used to protect an inheritance from the actions of an heir who can make a will which deviates from an absolute part (legitime portie). An absolute part (legitime portie) is protected by a law, this is because in an absolute part (legitime portie) there’s a right that can be used to make a claim to the court in order to obtain a part of its rights an inheritance that’s and has been regulated in a will.